Valuation Under Rapidly Changing Periods - Ab Rahman, Rosdi; Sipan, Ibrahim @ Atan (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1997)
Over the years we have experience several situations that have tarnished the image of the valuation profession. The phenomenon was more apparent when the market is going through a down surge and worst of all when it slumps to the lowest revel. Even though this trend is expected by most of the players in the property industry (particularly the investors and bankers), they didn't seem to appreciate it when it happened. Thus, they start looking for scapegoats to cover-ups for any slack in the prior investment decision made. Experience has shown that in the slowdown of mid 80's, valuers were made as the scapegoat and the profession had to suffer. These allegations and condemnation were definitely uncalled for but then again we also heard or came across odd and isolated cases of incompetent or negligent valuers. Simplified valuation and overvaluation were amongst the few shortcomings aired. To add to the matter, we recently heard complaints coming from distinguished personality about cases of undervaluation. Either way, these would not be good for the profession. The problem could be even more serious especially we are going through these rapidly changing periods. Accordingly, this paper is prepared to explore the need and expectation of valuation exercise. Hopefully it can and will be translated into the practice of carrying out the exercise. The valuation outcome will then be more relevant and acceptable and it should assist to rule out the possibility of another slandering and simultaneously improve and better the image of the valuation profession.